ChemInform Abstract: Rapid Synthesis of Fused N‐Heterocycles by Transition‐Metal‐Free Electrophilic Amination of Arene C—H Bonds. Issue 32 (24th July 2014) - Gao, Hongyin; Xu, Qing‐Long; Yousufuddin, Muhammed; Ess, Daniel H.; Kuerti, Laszlo
Abstract: The synthesis of fused N‐heterocycles starting from readily available 2‐nitrobiaryls and phenylmagnesium bromide is disclosed.